2008
DOI: 10.5194/acp-8-3623-2008
|View full text |Cite
|
Sign up to set email alerts
|

The role of iron and black carbon in aerosol light absorption

Abstract: Abstract. Iron is a major component of atmospheric aerosols, influencing the light absorption ability of mineral dust, and an important micronutrient that affects oceanic biogeochemistry. The regional distribution of the iron concentration in dust is important for climate studies; however, this is difficult to obtain since it requires in-situ aerosol sampling or simulation of complex natural processes. Simultaneous studies of aerosol chemical composition and radiometric measurements of aerosol optical properti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 83 publications
4
51
0
Order By: Relevance
“…5), also reported in Table 3, ranged from 2.8 % (Namibia) to 7.3 % (Australia). These are in the range of values reported in the literature, taking into account that differences might be also due to the method (direct measurement/calculation) and/or the size fraction over which the total dust mass concentration is estimated (Chiapello et al, 1997;Reid et al, 1994;Derimian et al, 2008;Formenti et al, 2001Formenti et al, , 2011Formenti et al, , 2014aScheuvens et al, 2013). The agreement of MC Fe% values obtained by the XRF analysis of polycarbonate filters (Eq.…”
Section: Elemental Composition and Iron Oxide Contentsupporting
confidence: 65%
See 1 more Smart Citation
“…5), also reported in Table 3, ranged from 2.8 % (Namibia) to 7.3 % (Australia). These are in the range of values reported in the literature, taking into account that differences might be also due to the method (direct measurement/calculation) and/or the size fraction over which the total dust mass concentration is estimated (Chiapello et al, 1997;Reid et al, 1994;Derimian et al, 2008;Formenti et al, 2001Formenti et al, , 2011Formenti et al, , 2014aScheuvens et al, 2013). The agreement of MC Fe% values obtained by the XRF analysis of polycarbonate filters (Eq.…”
Section: Elemental Composition and Iron Oxide Contentsupporting
confidence: 65%
“…Balkanski et al (2007) showed that lowering the dust absorption properties to an extent that reconciles them both with the remote-sensing observations and the state of knowledge of the mineralogical composition allowed calculating the clear-sky shortwave radiative effect of dust in agreement with satellite-based observations. A significant number of observations have quantified the shortwave lightabsorbing properties of mineral dust both by direct measurements Linke et al, 2006;Osborne et al, 2008;McConnell et al, 2008;Derimian et al, 2008;Yang et al, 2009;Müller et al, 2009;Petzold et al, 2009;Moosmüller et al, 2012;Wagner et al, 2012;Ryder al., 2013a;Utry et al, 2014;Denjean et al, 2016a, b) and indirectly by quantifying the amount and the speciation of the light-absorbing compounds in mineral dust, principally iron oxides (Lafon et al, , 2006Lazaro et al, 2008;Derimian et al, 2008;Zhang et al, 2008;Kandler et al, 2007Kandler et al, , 2009Kandler et al, , 2011Formenti et al, 2014a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm then retrieves a size distribution dominated by non-spherical coarse-mode particles that shows much smaller absorption properties than biomass-burning aerosols. Mineral dust particles also absorb the solar light due to the presence of iron oxide in their mineral composition (Derimian et al, 2008a). However, dust remains less absorbing than biomass-burning aerosols, except probably for cases where it is mixed with carbonaceous material (Derimian et al, 2008b).…”
Section: Case Of Mineral Dust Particles Above Cloudsmentioning
confidence: 99%
“…Doherty et al (2010) estimated that between 20% and 50% of the light absorption by particles in snowpack is caused by organic ("brown") carbon and dust. The MAC of particulate organic matter ranges from 0.25 m 2 /g to 1.5 m 2 /g at 404 nm (Lack et al 2013) and that of mineral dust is about 1.3 m 2 /g at 440 nm (Derimian et al 2008). If most of the coarse particulate matter and 25% of fine particulate matter were dust and organic matter, these particles provide about 50% of the total particulate mass compared to 3% for BC at this station (based on average concentrations measured by the IMPROVE network).…”
Section: Uv/vis Spectrophotometermentioning
confidence: 99%